Development methodology on determination of instant release fractions for generic safety assessment for direct disposal of spent nuclear fuel - AKAHORI, Kuniaki; KITAMURA, Akira; NAGATA, Masanobu (Journal of Nuclear Fuel Cycle and Environment, 2020)
Direct disposal of spent nuclear fuel (SNF) in deep underground repositories (hereafter “direct disposal”) is a concept that disposal canisters stored fuel assemblies dispose without reprocessing. Behavior of radionuclide release from SNF must be different from that from vitrified glass. The present study established a methodology on determination of instant release fraction (IRF) of radionuclides from SNF, which is the one of the parameters on radionuclide release based on the latest safety assessment reports in other countries, especially for IRF values proportional to a fission gas release ratio (FGR). Recommended and maximum values of FGR have been estimated using the fuel performance code FEMAXI-7 after collecting FGR values on Japanese SNFs. Furthermore, recommended and maximum values of IRF for Japanese SNFs used in a pressurized water reactor (PWR) have been estimated using the presently obtained FGR values and experimentally obtained IRF values on foreign SNFs. The recommended and maximum IRF values obtained in the present study have been compared with those of the latest safety assessment reports in other countries.